Crossing Borders, Casting Votes: Examining Migrant Electoral Turnout in Chile (2012–2020) - Herrrera, M (Routledge, 2024)
Our analysis focuses on the determinants of electoral participation among migrants, considering individual factors—gender and age—and variables from their countries of origin, such as economic, political, and institutional aspects. We specifically look at Chile, where migrants are allowed to vote in all elections after acquiring five years of permanent residency. Utilizing a comprehensive administrative census covering over 70 million voters, including 1.2 million migrants, from 2012 to 2020, our findings reveal several key patterns: Gender and age significantly influence voting behavior, with higher turnout among women and older migrants. Additionally, migrants from wealthier nations tend to vote less compared to those from poorer countries. Furthermore, the presence of compulsory voting in the origin country significantly increases participation among migrants, especially those from less democratic or non-democratic countries. This study bridges theoretical models that focus on individual variables and those that emphasize the impact of origin country characteristics on migrant electoral behavior. © 2024 Informa UK Limited, trading as Taylor & Francis Group.